2008
DOI: 10.1021/jp8066519
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Intramolecular Hydrogen Transfer between Protein Cysteine Thiyl Radicals and αC−H Bonds in Insulin: Control of Selectivity by Secondary Structure

Abstract: The selective oxidative modification of proteins can have significant consequences for structure and function. Here, we show that protein cysteine thiyl radicals (CysS*) can reversibly abstract hydrogen atoms from the alpha C-H bonds of selected amino acids in a protein (insulin). CysS* were generated photolytically through homolysis of cystine and through photoionization of an aromatic residue, followed by one-electron reduction of cystine. Intramolecular hydrogen transfer was monitored through the covalent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(70 citation statements)
references
References 43 publications
(75 reference statements)
1
69
0
Order By: Relevance
“…The side-chain thiolate radicals of cysteine residues represent an important class of radicals in peptide and protein chemistry that are involved in a number of enzyme reactions [24] and are implicated in protein damage [25]. Recent work by Schoeneich's group has demonstrated that the side-chain thiolate radicals of cysteine residues can abstract hydrogen atoms from amino acids intermolecularly and also intramolecularly from adjacent amino acid residues [67][68][69][70][71][72]. Given the potential importance of these reactions in protein damage, as well as these being excellent model systems to examine side-chain-to-backbone HAT in gas-phase peptides, here we use a combination of multistage mass spectrometry experiments, collision-induced dissociation, deuterium labeling, and density functional theory (DFT) calculations to study the fragmentation reactions of regiospecifically generated radical cations of simple cysteine-containing di-and tripeptides.…”
mentioning
confidence: 99%
“…The side-chain thiolate radicals of cysteine residues represent an important class of radicals in peptide and protein chemistry that are involved in a number of enzyme reactions [24] and are implicated in protein damage [25]. Recent work by Schoeneich's group has demonstrated that the side-chain thiolate radicals of cysteine residues can abstract hydrogen atoms from amino acids intermolecularly and also intramolecularly from adjacent amino acid residues [67][68][69][70][71][72]. Given the potential importance of these reactions in protein damage, as well as these being excellent model systems to examine side-chain-to-backbone HAT in gas-phase peptides, here we use a combination of multistage mass spectrometry experiments, collision-induced dissociation, deuterium labeling, and density functional theory (DFT) calculations to study the fragmentation reactions of regiospecifically generated radical cations of simple cysteine-containing di-and tripeptides.…”
mentioning
confidence: 99%
“…The deuterium content of peptide ions and their fragments was determined from the differences between the average mass of a covalently deuterated peptide and the average mass of the corresponding fully protonated peptide, according to our published protocol (22). The average masses were calculated from centroided isotopic distributions.…”
Section: Covalent H/d Exchange and Isotopic Correctionmentioning
confidence: 99%
“…The distribution of deuterium incorporation was obtained after isotopic correction by subtracting the isotope abundance distribution in the product formed during UV-irradiation in H 2 O from the isotope abundance distribution of the same product generated in D 2 O. This variation of the isotopic distribution between the experiments performed in deuterium oxide solution and water is given by the variation of the percent base peak intensity (%ΔBPI) (22).…”
Section: Covalent H/d Exchange and Isotopic Correctionmentioning
confidence: 99%
See 2 more Smart Citations